1995
DOI: 10.1073/pnas.92.20.9151
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the presence of a protease-activated receptor distinct from the thrombin receptor in human keratinocytes.

Abstract: Thrombin receptor activation was explored in human epidermal keratinocytes and human dermal fibroblasts, cells that are actively involved in skin tissue repair. The effects of thrombin, trypsin, and the receptor agonist peptides SFLLRN and TFRIFD were assessed in inositolphospholipid hydrolysis and calcium mobilization studies. Thrombin and SFLLRN stimulated fibroblasts in both assays to a similar extent, whereas TFRIFD was less potent. Trypsin demonstrated weak efficacy in these assays in comparison with thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

17
131
3

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(153 citation statements)
references
References 23 publications
17
131
3
Order By: Relevance
“…Thrombin, a serin protease that plays an important role in the blood coagulation cascade through its cleavage of fibrinogen to fibrin, has been reported to have hormone-like receptor-mediated effects in various types of cells, including bone cells (Fenton 1988). On activation, these receptors signal via intracellular calcium and prostaglandin formation and the thrombin receptor responds to the activating peptide in a manner previously described (Santulli et al 1995).…”
Section: Discussionmentioning
confidence: 97%
“…Thrombin, a serin protease that plays an important role in the blood coagulation cascade through its cleavage of fibrinogen to fibrin, has been reported to have hormone-like receptor-mediated effects in various types of cells, including bone cells (Fenton 1988). On activation, these receptors signal via intracellular calcium and prostaglandin formation and the thrombin receptor responds to the activating peptide in a manner previously described (Santulli et al 1995).…”
Section: Discussionmentioning
confidence: 97%
“…Recently, PAR-1 expression has been reported in neurons of the ENS (Corvera et al 1999). PAR-2 is also widely expressed; it has been demonstrated in vascular tissue, the digestive system and epidermis (Al-Ani et al 1995 21 ; Santulli et al 1995;Derian and Eckardt 1997;D'Andrea et al 1998;Corvera et al 1999). Within the gastrointestinal tract, PAR-2 has been reported in enterocytes, smooth muscle cells and myenteric neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Effects of PAR-1 and PAR-2 Activation on Adhesion of MKN-1 Cells-It has been reported that trypsin activates PAR-2 efficiently, stimulating signal transduction through G proteins (23,25). Therefore, the activation of PARs seemed to be a possible mechanism for the stimulatory effect of trypsin on adhesion of MKN-1 cells to fibronectin.…”
Section: Effect Of Trypsin On Adhesion Of Mkn-1 Cells To Variousmentioning
confidence: 99%
“…PAR-1 (thrombin receptor) and PAR-3, which are expressed mainly in platelets, endothelium, and leukocytes, are effectively activated by thrombin (23,24). In contrast, PAR-2, which is expressed in a wide variety of epithelial tissues, endothelial cells, T cells, smooth muscle cells and tumor cell lines, is activated by trypsin but not by thrombin (22,(25)(26)(27). Recently found PAR-4 is highly expressed in the lung, thyroid, testis, and small intestine, and activated by both thrombin and trypsin (28).…”
mentioning
confidence: 99%
See 1 more Smart Citation